THE ANALYSIS OF FACTORS AFFECTING THE PERFORMANCE AND BENEFIT OF KARAPAN (RACING) CATTLE BUSINESS IN MADURA ISLAND, EAST JAVA, INDONESIA - Riszqina, Riszqina; Isbandi, Isbandi; Rianto, E.; Santoso, S.I. (Diponegoro University, 2014)
A research was carried out to analyze the influence of productive factors on the performance ofkarapan (means racing) cattle business in Madura Island, East Java Province, Indonesia. The researchwas conducted by a survey method, with 135 karapan cattle farmers as respondents in regencies ofBangkalan, Sampang, Pamekasan and Sumenep (mainland). The data were collected in the period ofApril to August 2012. Data of zootechnique indicators variables, farmer’s motivation, allocation time oflabour, labour skills, business scale, productivity of karapan cattle, farmers' performance and benefit ofkarapan cattle business were analysed by Lisrel 8.8 program. The results showed that factors ofzootechnique, farmer’s motivation, labour skills and business scale had highly significant influence(P<0.01) on productivity of karapan cattle, but allocation time of labour did not have significantinfluence (P>0.05). The performance of karapan cattle business was highly influenced by productivity ofkarapan cattle (P<0.01). The benefit of karapan cattle business was influenced (P<0.01) by performanceof karapan cattle business. It is concluded that the farmer's benefit of karapan cattle business wasinfluenced by performance of karapan cattle, which in turn was influenced by productivity of thekarapan cattle.